PERHITUNGAN BREAK EVEN POINT SEBAGAI ALAT PERENCANAAN PENJUALAN DAN LABA PADA UMKM DI KELURAHAN KEMBANGAN SELATAN JAKARTA BARAT - Silaban, Anna Christin; Murtiningsih, Dewi (Jurnal Pengabdian Bukit Pengharapan, 2024)
Micro and Medium Enterprises or MSMEs in Indonesia have experienced continuous growth. To encourage business people to run their businesses so as not to experience losses, knowledge of break even point calculations is needed as a sales and profit planning tool. For this reason, training was carried out for MSME business actors in the South Kembangan area by introducing Break Even Point accounting calculations. Through this education, it is hoped that it can support the success of MSMEs which will improve the standard of living and economy of MSMEs.